PEMBUATAN PROSEDUR DAN FORMULIR SERVICE DESK PEMERINTAHAN KOTA MADIUN BERDASARKAN ITIL V3 - Effendi, Zulaikah; Herdiyanti, Anisah; Susanto, Tony Dwi (Department of Information Systems, Institut Teknologi Sepuluh Nopember, 2019)
The Government of Madiun City is committed to apply Smart City concept by implementing Madiun Service Desk (MSD) to support e-government. However, the implementation of MSD application is not yet equipped with an operational standard for delivering information technology (IT) services to the consumers. Meanwhile, the IT services are handled by a Service Desk who ensures that the service levels are adhered, and requests are fulfilled. This research focuses on the development of standard operating procedures (SOPs), including procedures and forms to support their operations. Prior to the development of the SOPs, an information gathering was performed to understand the landscape of Service Desk. Then, a gap analysis was conducted based on the landscape and the standardized operations according to ITIL V3. The results from the research includes 4 (four) procedures, and 8 (eight) forms that has been validated by Service Desk in the Madiun City.